The effect of cytomegalovirus on clinical and paraclinical as well as immune parameters of children with rotavirus infection - M. Yu. Sliepchenko; S. V. Kuznetsov (Patologìâ)
The aim is to evaluate the effect of cytomegalovirus on clinical and paraclinical as well as immunological parameters in children with rotavirus infection (RVI).